A semi-analytical numerical method for fast metamaterial absorber design - Y. C. Song; J. Ding; C. J. Guo (AIP Advances, 2015)
In this paper, a semi-analytical numerical approach utilizing a novel non-grounded model and interpolation technique is introduced to design the frequency selective surface (FSS) based metamaterial absorbers (MAs) with dramatically reduced time consumption. Different from commonly used trial-and-error technology, our method mainly utilize the numerically computed FSS layer impedance with slow-varying feature in the vicinity of operating frequency. The introduced non-grounded model establishes the quantitative relationship between geometry parameters and equivalent lumped circuit components in conventional transmission line (TL) model with reasonable accuracy. The interpolation technique, on the other hand, promises a relative sparse parameter sweep. The detailed design flow as well as analytical explanation with carefully deduced expressions is presented. With the purpose of validating the proposed method and analytical models, a MA with slotted patches is designed through both the semi-analytical numerical approach and the trial-and-error method, where an over 2300 times acceleration is observed. Additionally, results from the analytical computation and full wave simulation agree well with each other.